The primate origins of human nature - Schaik, Carel van, 4 0 16; 5 (Hoboken, New Jersey : Wiley-Blackwell, 2016)
The Primate Origins of Human Nature brings a multi-disciplinary, multi-theory, and deeply comparative perspective to the contested idea of human nature. Drawing on the findings and concepts of classical physical anthropology, behavioral ecology, and comparative and evolutionary psychology, this book uncovers and traces primate antecedents and evolutionary causes for a broad range of supposedly unique features of human social organization, life history, and behavior, from aesthetics to xenophobia. --;Authored by a leading researcher and theorist in the study of human and primate behavioral evolution, The Primate Origins of Human Nature is not only an invaluable resource for both students and researchers, but also a creative and ground-breaking synthesis of current knowledge in the biological and social sciences that illuminates the origins and nature of humanity. --;By integrating up-to-date interdisciplinary concepts from a wide variety of academic disciplines, this work prepares readers to understand and engage in current debates over how humans came to be. --;Bridges the studies of primatology and anthropology by taking a broad comparative approach --;Effectively primes the reader on both primate behavioral biology and human evolution --;Is strongly multi- and inter-disciplinary throughout, offering students a very broad view of the field --;Is designed to serve as both a textbook and a reference work for researchers in the field --Book Jacket.
Evolution, Behavior and Culture. Elements of Evolutionary Biology -- Basics of Behavioral Biology -- Social Learning and Culture -- Evolution and Human Behavior -- The History of Humans. Ancestors: Humans from a Comparative Perspective -- Human Evolution: A Brief Overview -- Subsistence and Technology. Primate Ecology -- Forager Ecology and Subsistence -- The Evolution of Technology -- Sex and Sexual Selection. Sex, Sexual Selection and Sex Differences -- Mating Systems and Sexuality in Primates -- Human Mating Systems and Sexuality -- Aesthetic Appreciation and Expression -- Life's Changes. Life History -- Parenting and Reproductive Investment -- Growth and Development -- Social Life. Social Life in Nonhuman Primates -- Primate Socioeclogy -- Social Evolution in Hominins -- Cooperation. Cooperation in Nature -- Warfare -- Morality -- Religion -- The Cognitive Animal. The Evolution of Brain Size -- The Evolution of Primate Cognition -- Human Language -- Conclusions. What Made Us Humans? A Preliminary Synthesis.
Includes bibliographical references and index.
Online resource; title from PDF title page (John Wiley, viewed February 8, 2016).
Keywords: 2 -- 0; 6; Behavior.;Behavior. -- Human evolution.;Evolutionary psychology.;Human behavior.;Primates;Physical anthropology.;Evolutionary psychology.;Human behavior.;Human evolution.;Physical anthropology.;Primates; 20; Electronic books. -- 2